AGE AND GROWTH OF RIBBONFISH TRICHIURUS LEPTURUS LINNAEUS - Narasimham, K A (Indian Journal of Fisheries, 2011)
The ribbonfishes form an important group of food fish along theAndhra coast and among them Trichiurus lepturus Linnaeus is the dominantspecies. Except for the work of Prabhu (1955) and some comments by Tampiet al (1971), there is no other published information from Indian waters onage and growth of the species. This aspect has been dealt with in this article.